Electric drive with common rectifier and individual inverters of wood processing line of Amur timber processing plant - V. S. Klimash; A. V. Petukhov (Омский научный вестник)
In the article the power supply system of the electric drive of a woodworking line is considered. A special feature of the electric drive is the method of connecting the autonomous inverters to the direct current source through a common link of a constant voltage. The result of using the power supply system is the saving of electricity by eliminating braking resistors from the circuit and normalizing the thermal regime in the electronic control system. The results of a study of physical processes obtained in the process of simulation modeling are presented.